1997
DOI: 10.1016/s0014-5793(97)00105-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of firefly luciferase shows that cysteine residues are not required for bioluminescence activity

Abstract: Conflicting reports exist in the literature as to whether sulfhydryl groups are essential for firefly luciferase activity. Inactivation of Photinus pyralis luciferase with ./V-tosyl-L-phenylalanine chloromethyl ketone (TPCK) and site-directed mutagenesis demonstrate that the cysteine residues are not absolutely required for activity. However, loss of P. pyralis luciferase activity is observed when any of the 4 cysteine residues is replaced with serine.© 1997 Federation of European Biochemical Societies.Key wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In addition, there was close sequence homology between the cysteine domains of the luciferases in seven species of firefly. However, firefly luciferase is active after cysteine modification (47). It is also interesting to note that pholasin contains no histidine residues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was close sequence homology between the cysteine domains of the luciferases in seven species of firefly. However, firefly luciferase is active after cysteine modification (47). It is also interesting to note that pholasin contains no histidine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Two sulfhydryl groups in firefly luciferase were originally suggested to be important for catalysis in bioluminescence [113,114], however, recent investigations show that no sulfhydryl group is essential for activity [115,116]. The deletion of the last C-terminal 12 residues in firefly luciferase results in complete loss of activity [117], showing that the C-terminal domain is essential for activity.…”
Section: Structure-function In Beetle Luciferasesmentioning
confidence: 99%
“…We chose to utilize firefly luciferase to develop this misincorporation reporter system due to the availability of its crystal structure and the many genetic studies previously carried out with this protein. [14][15][16][17][18][19][20][21] In those studies, it was shown that the His residue encoded at position 245 (His245 (CAC)) and the Lys residue encoded at position 529 (Lys529 (AAA)) each play an important role in the enzymatic activity of firefly luciferase, [15][16][17] probably because these residues properly orient the substrate and stabilize the transition state of the enzyme. It was previously reported that Lys529 is essential for enzymatic activity, 17 while His245 is important, but not absolutely essential.…”
Section: Introductionmentioning
confidence: 99%